PTU-079 Assessing gluten free diet adherence using cdat and biagi questionnaires in patients with coeliac disease. (June 2019) - Baggus, Ms Elisabeth; Rej, Anupam; Lau, Michelle; Mooney, Peter; Rees, Mr Micheal; White, Mr William; Marks, Ms Lauren; Hadjivassiliou, Marios; Sanders, David
Abstract : Introduction: The gold standard currently for assessing adherence in individuals with coeliac disease is via duodenal biopsies, which is invasive and costly. In view of this, we assessed the utility of the CDAT and Biagi questionnaires for non-invasive assessment of gluten free adherence. Methods: Patients with an established diagnosis of coeliac disease, referred for further evaluation of dietary adherence and disease remission were assessed between January 2016 to December 2018. Patients were prospectively recruited, and completed CDAT and Biagi questionnaires, with at least 4 duodenal biopsies taken from D2 in addition to at least one biopsy from the duodenal bulb. The presence (Marsh 3a or above) or absence (Marsh 0-II) of villous atrophy was used to determine the sensitivities of the tests. Results: 151 patients were recruited, 101 females (66.9%), median age 55.0 years, median duration of GFD of 72.0 months. Table 1 outlines the sensitivity and specificity of the CDAT questionnaire, Biagi questionnaire, IgA-TTG and IgA-EMA. Conclusions: The sensitivity of the CDAT questionnaire was not superior to IgA-TTG for predicting villous atrophy in patients with coeliac disease. However, the use of a combination of both Biagi and CDAT had a greater sensitivity than IgA-TTG and IgA-EMA (p<0.05), but lower specificity (p<0.05). Duodenal biopsy remains the gold standard, although these scores remain useful tools in the assessment of dietary adherence.